Nuclear Localization of IκBα Is Mediated by the Second Ankyrin Repeat: the IκBα Ankyrin Repeats Define a Novel Class of cis-Acting Nuclear Import Sequences - Sachdev, Shrikesh (American Society for Microbiology, 1998)
The ability of the IκBα protein to sequester dimeric NF-κB/Rel proteins in the cytoplasm provides an effective mechanism for regulating the potent transcriptional activation properties of NF-κB/Rel family members. IκBα can also act in the nucleus as a postinduction repressor of NF-κB/Rel proteins. The mechanism by which IκBα enters the nucleus is not known, as IκBα lacks a discernible classical nuclear localization sequence (NLS). We now report that nuclear localization of IκBα is mediated by a novel nuclear import sequence within the second ankyrin repeat. Deletion of the second ankyrin repeat or alanine substitution of hydrophobic residues within the second ankyrin repeat disrupts nuclear localization of IκBα. Furthermore, a region encompassing the second ankyrin repeat of IκBα is able to function as a discrete nuclear import sequence. The presence of a discrete nuclear import sequence in IκBα suggests that cytoplasmic sequestration of the NF-κB/Rel–IκBα complex is a consequence of the mutual masking of the NLS within NF-κB/Rel proteins and the import sequence within IκBα. Nuclear import may be a conserved property of ankyrin repeat domains (ARDs), as the ARDs from two other ARD-containing proteins, 53BP2 and GABPβ, are also able to function as nuclear import sequences. We propose that the IκBα ankyrin repeats define a novel class of cis-acting nuclear import sequences.